A study on Bumiputra quota in housing area, its implementation and methods to standardize the implementation / Aimi Nasruddin Mohd Roslan...[et al.] - Mohd Roslan, Aimi Nasruddin; Abdul Hamid, Elfira Rosellini; Mahmod, Muhammad Azfar; Rosli, Nur Izzati (Faculty of Law, 2013)
Currently Malaysia is facing issue of implementating bumiputra quota on housing development. The objective is to focus on the method to standardize its implementation on housing area. Regarding to this situation, a doctrinal research needs to be done to analyze the issue of bumiputra quota implementation in housing area. The research will be a library-based research and internet-based research. Library-based research is to obtain information regarding the various implementations of the scheme on selected states of Kedah, Johor and Penang. Whereas internet-based research will be to gather various articles published regarding relevant real estate issues that are related to implementation of the bumiputra quota. The findings between these different states are compared to find out the different methods of implementation. From these findings, the researchers had used it to identify the main problem and figure out a solution to solve this problem. It is identified that the implementation of different states were indeed different and was far from the objectives of the bumiputra quotas set by the New Economic Model. The researchers made a conclusion that this issue has been getting out of hand and that no action has been taken to overcome this problem. The researchers suggest that the problem to be tackled through methods of implementing a specific uniform bumiputra quota in housing development for all States in Malaysia and method of release clause of the bumiputra lot allocation rule.